A fire truck for Chuck - Dunklee, Annika, 1965- (Owlkids Books, 2018)
"At a yard sale with his mom, Chuck spots a fire truck. It only costs a buck--what luck! Mom buys Chuck the truck, and he loves everything about it. At home, he plays with it nonstop. But after bath time, his fire truck is nowhere to be seen! Dumbstruck, Chuck hunts all over the house. Where is his truck?! Was it sucked up into the vacuum, now stuck? Finally, Chuck and his truck are reunited, just in time for bed. Told with plenty of fun rhyme and repetition, this story's bright, cartoon-like art conveys Chuck's full range of emotions. Full of humor and warmth, it's a lovable read-aloud that captures a child's joy for their favorite toy."--